Carotenoid Production of Rhodosporodimum Toruloides under Light Irradiation - Pham, Khanh Dung; Ogasawara, Wataru; Tran, Van Hung (Journal of Technical Education Science, 2023)
Carotenoids are widely used as an antioxidant, a precursor to vitamin A, and food colorants in the medical, cosmetic, chemical, food, and feed industries. They were distributed in diverse microorganisms including bacteria, algae, and fungi. Among them, the yeast Rhodosporidium toruloides is convenient for large-scale fermentation due to its unicellular nature and high growth rate. However, many factors influence the biotechnological synthesis of carotenoids. Light is a crucial consideration while making microbial carotenoids. Carotenogenic is a photo-protective technique used by microorganisms to defend themselves from the light that causes oxidative damage. R. toruloides raised their carotenoid productivity under light conditions in this study. Various lights were used to compare the effect of color light in carotenoid productivity. Results showed that R. toruloides produced more carotenoid content when cultured in blue or white light as compared to a red light or in the dark. Besides, results from microarray showed that this light influence was in the transcription gene level, the light irradiation encouraged the formation of antioxidants such carotenoids, causes a protective mechanism against DNA damage and oxidative stress.